Practicing Transdisciplinarity and Trans-Domain Approaches in Education: Theory of and Communication in Values and Knowledge Education (VaKE) - Jean-Luc Patry (Journal of Systemics, Cybernetics and Informatics)

(untitled)
(Academic) disciplines are a means to structure science and are not appropriate for epistemic discussions. Instead, it is proposed to use the concept of Trans-Domain Approaches (TDA). A TDA typically consists in a General Theory GT that integrates and transcends the Domain-Specific Theories (DTs) referring to a re-search topic. The constructivist teaching-learning tool Values and Knowledge Education (VaKE) is used as a prototype to an-alyze different features of a TDA. First, the theoretical frame-work of VaKE is analyzed under the perspective of TDA: VaKE integrates several constructivist theories, particularly about moral judgment competence, constructivist knowledge acquisi-tion, and social constructivism. Then, the communication be-tween stakeholders is analyzed more in detail, based on Shannon and Weaver's channel model. The analyses focus on communi-cation among researchers, between researchers and practitioners (teachers), between practitioners and students, and among stu-dents. Several conclusions with respect to TDA can be drawn.